Rodent Cells Support Key Functions of the Human Immunodeficiency Virus Type 1 Pathogenicity Factor Nef - Keppler, Oliver T. (American Society for Microbiology, 2005)
After infection with human immunodeficiency virus (HIV), progression toward immunodeficiency is governed by a complex interplay of viral and host determinants. The viral accessory protein Nef is a key factor for the development of AIDS. Strains of HIV and simian immunodeficiency virus that lack functional nef genes either do not induce AIDS or do so only after a significant delay. The validity of a transgenic-small-animal model for de novo infection by HIV will depend on its ability to recapitulate the actions of critical factors of viral pathogenicity, such as Nef. We assessed the ability of rat, mouse, and hamster cells to support key effector functions of Nef. In cell lines from rodents, the subcellular distribution of wild-type HIV type 1 strain SF2 Nef and mutants was comparable to that in human cells. Nef downregulated human CD4 from the cell surface, was associated with p21-activated kinase activity, and enhanced the infectivity of HIV-1 virions. Importantly, these Nef-induced effects, as well as the downregulation of rat CD4 and major histocompatibility complex class I molecules, could also be demonstrated in primary T lymphocytes and macrophages from human CD4-transgenic rats. Thus, HIV-1 Nef exerts key functions in rodent cells. In line with our ongoing efforts to establish a transgenic-rat model of HIV disease, these results indicate that important aspects of viral pathogenesis could be addressed in a transgenic-rodent model permissive for de novo infection and that such a model would be valuable for evaluating the function of Nef in vivo.